Identification and Characterization of Bacillus subtilis B9: A Diazotrophic Plant Growth-Promoting Endophytic Bacterium Isolated from Sugarcane Root - Yi-ning Di; Ling Kui; Pratiksha Singh; Lu-feng Liu; Lin-yan Xie; Li-lian He; Fu-sheng Li (Journal of Plant Growth Regulation, 2023)
Plant endophytic microorganisms, which can enhance plant growth and resistance to biotic and abiotic stresses, are untapped resources with large potential applications for crop production. However, the endophytic community is influenced by multiple factors, such as host genetics, the environment, and other microbes. Thus, it is important to characterize well-adapted endophytes from native crops. We isolated 43 endophytic bacteria from sugarcane cultivar Yunzhe-99-91. All these 43 isolates were examined in vitro for nitrogenase activity and the ability to dissolve phosphorus and produce siderophore. One of these strains, B9, identified as Bacillus subtilis and showed maximum plant growth promotion, was selected for detailed studies. B9 promoted the production of organic acids such as propionic acid, acetic acid, malic acid and citric acid, and the production of phytohormones, including indole-3-acetic acid, cytokinin, 6-benzyladenine, and zeatin. Moreover, B9 significantly promoted the growth of sugarcane plantlets and increased the content of nitrogen, phosphorus, and potassium in the seedlings by 29.26%, 50.78%, and 15.49%, respectively. The photosynthetic rate, root development, and chlorophyll content were also improved with varying degrees compared to the non-inoculated control. The cotyledon and hypocotyl of sugarcane gems germinated faster when co-cultured with the B9 strain compared with control group. Colonization assay showed that B9 was mainly colonized in the roots, followed by the stems and leaves. In conclusion, the positive interaction between endophytic strain B9 and sugarcane may provide long-lasting benefits and a direction for developing and utilizing B9 as a biofertilizer for sugarcane cultivation to decrease fertilizer application.